Phase 1 trial of ibrutinib and carfilzomib combination therapy for relapsed or relapsed and refractory multiple myeloma. Issue 11 (2nd November 2018) - Chari, Ajai; Larson, Sarah; Holkova, Beata; Cornell, Robert F.; Gasparetto, Cristina; Karanes, Chatchada; Matous, Jeffrey V.; Niesvizky, Ruben; Valent, Jason; Lunning, Matthew; Usmani, Saad Z.; Anderson, Larry D.; et al.
Abstract: This phase 1, dose-finding study investigated ibrutinib and carfilzomib ± dexamethasone in patients with relapsed or relapsed/refractory multiple myeloma (≥2 lines of therapy including bortezomib and an immunomodulatory agent). Of 43 patients enrolled, 74% were refractory to bortezomib and 23% had high-risk cytogenetics. No dose-limiting toxicities were observed. The recommended phase 2 dose was ibrutinib 840 mg and carfilzomib 36 mg/m 2 with dexamethasone. The most common ≥ grade 3 (>10%) treatment-emergent adverse events were hypertension, anemia, pneumonia, fatigue, diarrhea, and thrombocytopenia. Overall response rate was 67% (very good partial response, 21%; stringent complete response, 2%), with an additional 9% minimal response. Median progression-free survival was 7.2 months and was not inferior in refractory nor high-risk patients. Median overall survival was not reached. Ibrutinib plus carfilzomib demonstrated encouraging responses with a manageable safety profile in this advanced population.